Semiotic Analysis of The Denotative and Connotative Meaning on The Beatles’ Songs Lyrics - Rizky Ishar; Andi Muhammad Irawan (English Language and Literature, 2023)
This study examines semiotics analysis on five Beatles songs, namely Hey Jude, Here Comes The Sun, Come Together, Yesterday, and Let It Be by using Roland Barthes' semiotic theory of signs. This study aims are to investigate the denotative and connotative meanings contained in the song lyrics and to examine myth in Barthes' theory by examining how the lyrics to The Beatles' song relate to the denotation and connotation meanings. This study is descriptive qualitative research method. The written text or transcript of the song lyrics served as the study data. There are 26 semiotic signs found in five songs of The Beatles which contents have denotative meaning, connotative meaning, and mythical meaning. There were 2 semiotic terms that were most manifested in the lyrics of the Beatles' Five songs namely: sincerity, and modesty or simplicity in life. These five songs of The Beatles can be used to represent characters, feelings, opinions, and experiences. The Myth's meaning emerges in the lyrics that hit much in reflecting human life, which touch on many aspects of human life.